Pengaruh Sosial Ekonomi terhadap Kemiskinan Energi Rumah Tangga di Indonesia - Adisti Aulia Sari; Mike Triani (Media Riset Ekonomi Pembangunan (MedREP), 2026)
Energy poverty is still a development challenge in Indonesia, marked by the continued use of wood as the main cooking fuel by some households. This situation shows that access to modern energy is still uneven. This study aims to analyze the influence of the household head's employment, housing conditions, number of household members, and household expenditures on energy poverty in Indonesia. The research uses a quantitative approach with secondary cross-sectional data from 38 provinces in 2024 sourced from the Central Statistics Agency (BPS). The analysis is conducted using multiple linear regression with the Ordinary Least Squares (OLS) method after passing the classical assumption tests. The research results show that, simultaneously, all independent variables have a significant effect on energy poverty. Partially, households with a working head of household have a positive and significant effect on energy poverty, while housing conditions and the number of household members have a negative and significant effect. Meanwhile, household expenditure has a negative but not significant effect. These findings indicate that energy poverty is not only influenced by household economic capacity but also by social characteristics and housing conditions that affect access to modern energy. Therefore, efforts to alleviate energy poverty need to be supported through improving job quality, upgrading housing conditions, and ensuring equal access to modern energy infrastructure and services. Keywords: energy poverty, housing conditions, working head of household, household expenditure, multiple linear regression.